Tetrakis(2-methylbenzimidazolium) β-octamolybdate(VI) - Hao, Lujiang (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, (C(8)H(9)N(2))(4)[Mo(8)O(26)], consists of two 2-methylbenzimidazolium cations and one-half of a β-Mo(8)O(26) (4−) anion, which is completed by crystallographic inversion symmetry. An extensive net of N—H⋯O hydrogen bonds between the cations and anions contribute to the crystal packing.